Chloroplast RNA Populations in Dark-Grown, Light-Grown, and Greening Euglena gracilis - Brown, Ronald D. (1971)
RNA preparations from dark-grown, light-grown, and greening Euglena gracilis have been compared by polyacrylamide gel electrophoresis and by hybridization to Euglena chloroplast DNA. Chloroplast ribosomal RNA is not detected in dark-grown cells; its abundance increases in greening cells over a 72 hr period until the concentration characteristic of light-grown cells is reached. Other RNA species complementary to chloroplast DNA are present in comparable abundance in light-grown, dark-grown, and greening cells.